ChemInform Abstract: Studies on the Oxidative Cyclization of 3‐Hydroxyalkyl‐1, 2, 4‐trialkoxynaphthalenes and Synthetic Application for the Biologically Active Natural Compound Rhinacanthone (XI). Issue 27 (8th July 2014) - Ogata, Tokutaro; Doe, Misae; Matsubara, Aya; Torii, Eri; Nishiura, Chiaki; Nishiuchi, Arisa; Kobayashi, Yusuke; Kimachi, Tetsutaro
Abstract The proposed mechanism suggests that the reaction proceeds by a stepwise oxidation‐cyclization sequence.